Sabinaria, a new genus of palms (Cryosophileae, Coryphoideae, Arecaceae) from the Colombia-Panama border - Bernal, Rodrigo; Galeano, Gloria (Phytotaxa, 2013)
The new palm genus Sabinaria (Cryosophileae, Coryphoideae, Arecaceae) and the new species Sabinaria magnifica from the Colombia-Panama border are described and illustrated. Sabinaria differs from other genera in the tribe in the leaf blades with a single deep, medial, abaxial split, and short abaxial splits in each segment, mostly unisexual flowers with biseriate perianth, calyx connate with the corolla at a single place on its margin, large, tightly appressed, persistent rachis bracts that hide the pistillate flowers, and fruits tightly packed and hidden among leaf bases, often covered by litter.  Se describen e ilustran el nuevo género de palmas Sabinaria (Cryosophileae, Coryphoideae, Arecaceae) y la nueva especie Sabinaria magnifica, de la frontera entre Colombia y Panamá. Sabinaria difiere de otros géneros en la tribu por la lámina foliar con una sola división abaxial central y cortas divisiones abaxiales en cada uno de los segmentos, flores principalmente unisexuales con perianto biseriado, cáliz connato con la corola en un solo punto en su margen, grandes brácteas del raquis fuertemente adpresas y persistentes, que ocultan las flores pistiladas, y frutos apiñados, ocultos entre las bases de las hojas y a menudo cubiertos por hojarasca.